Design and fabrication of modular supercapacitors using 3D printing. (April 2018) - Tanwilaisiri, Anan; Xu, Yanmeng; Zhang, Ruirong; Harrison, David; Fyson, John; Areir, Milad
Highlights: The paper presents a new method to fabricate supercapacitors using a combination of two different 3D printing techniques. A frame of supercapacitor with a hinge mechanism that can form a complete energy storage module without further assembly. A manufacturing process of supercapacitors can be achieved in one continuous process with high reproducibility. Abstract: Development in multi-material freeform 3D fabrication processes can provide the possibility of building complete functional electronic devices. This paper describes a design and manufacturing process for electrochemical supercapacitors. A combination of two 3D printing systems, i.e. a Fused Deposition Modelling (FDM) printer and a paste extruder, were applied to fabricate these energy storage devices. During the manufacturing process of supercapacitor components, the FDM 3D printer was used to print the packaging frames, the conductive layers, and the electrodes layers; and the separator with electrolyte were deposited using the paste extruder. Several complete energy storage supercapacitors have been made and their electrochemical performances were assessed. The 3D manufacturing process developed was also evaluated in this study.